Smoking behaviours and attitudes towards campus-wide tobacco control policies among staff and students: a cross-sectional survey at the University of Birmingham - Suzanne E. Bartington; Ruth Wootton; Philippa Hawkins; Amanda Farley; Laura L. Jones; Shamil Haroon (BMC, 2020)
Abstract Background Tobacco control policies have potential to be an effective strategy for the reduction of smoking prevalence and secondhand smoke (SHS) exposure in tertiary educational settings worldwide. The aims of this study were to collect baseline data among staff and students, to measure smoking behaviours and attitudes towards introduction of campus-wide tobacco control policies within a UK higher education setting. Methods Cross-sectional study using data collected by web-based questionnaire administered to employed staff and enrolled students (undergraduate/postgraduate) at the University of Birmingham from May 2016 to April 2017. Information was obtained regarding demographic characteristics, tobacco usage patterns and attitudes towards a revised campus tobacco control policy using a 21-item survey tool. Logistic regression analyses were used to explore associations between participant characteristics and support for smoke-free or tobacco-free campus policy options, evaluated by crude and adjusted Odds Radios (OR) after controlling for confounding factors (significance level: P < 0.05). Results A total of 934 survey responses were received, of whom 780 participants provided complete information on staff or student status and were included in the present analysis. Current smoking prevalence was 14% (N = 109; 95% confidence interval (CI) 11.6-16.6). Overall, 66.3% (95% CI: 62.9-69.7) of participants supported a smoke-free campus; 68.5% (95% CI: 65.2-71.8) endorsed restrictions for tobacco sales and just under half of respondents (47.3%; 95% CI: 43.8-50.9) supported a ban for electronic cigarettes/vaping device use on campus. Smoking status was an independent predictor of support for tobacco control, with the lowest level of support for a smoke-free campus among daily (adjusted OR 0.02; 95% CI: 0.01-0.05) and intermittent smokers (adjusted OR 0.06; 95% CI: 0.02-0.16). Conclusions Overall, the majority of staff and students participating in this baseline survey supported implementation of a smoke-free or comprehensive tobacco-free campus policy. These findings may inform the development and future implementation of a revised tobacco control policy at the university which reflects contemporary attitudes and considers a broad range of implementation issues, including behaviour change and environmental adaptations.